A Case Review on Combined Hepatocellular Cholangiocarcinoma. Issue 6 (November 2022) - Kondo, Reiichiro; Akiba, Jun; Yano, Hirohisa
Abstract: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver tumor with neoplastic components of both hepatocytic and cholangiocytic differentiation within the same tumor, such as the case reported herein. There is a need to standardize the pathological diagnosis of cHCC-CCA and to improve the concordance of diagnosis among pathologists based on consensus paper because of its histological and phenotypic diversity that leads to confusion in terminology and classification. This case review addresses the terminology, classification, and clinical and pathological characteristics of cHCC-CCA and its differential diagnosis.